2016
DOI: 10.1007/s00421-016-3480-1
|View full text |Cite
|
Sign up to set email alerts
|

Passive and post-exercise cold-water immersion augments PGC-1α and VEGF expression in human skeletal muscle

Abstract: PurposeWe tested the hypothesis that both post-exercise and passive cold water immersion (CWI) increases PGC-1α and VEGF mRNA expression in human skeletal muscle.Method Study 1 Nine males completed an intermittent running protocol (8 × 3-min bouts at 90 % , interspersed with 3-min active recovery (1.5-min at 25 % and 1.5-min at 50 % ) before undergoing CWI (10 min at 8 °C) or seated rest (CONT) in a counterbalanced, randomised manner. Study 2 Ten males underwent an identical CWI protocol under passive conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…In using that specific design, these data suggested that the effects of post‐exercise CWI previously observed by our laboratory (Joo et al. ) and others (Ihsan et al. , ) is regulated systemically via β‐adrenergic activation of AMPK (Allan et al.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…In using that specific design, these data suggested that the effects of post‐exercise CWI previously observed by our laboratory (Joo et al. ) and others (Ihsan et al. , ) is regulated systemically via β‐adrenergic activation of AMPK (Allan et al.…”
Section: Discussionsupporting
confidence: 56%
“…; Joo et al. ). Biopsies were obtained from both limbs at all time points to allow for comparison between low (LOW) and very low (VLOW) glycogen limbs in both CON and CWI trials.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…CWI, primarily as a result of its ability to decrease tissue temperature and blood flow (Gregson et al 2011;Costello et al 2012;Gregson et al 2013;Mawhinney et al 2013;Mawhinney et al 2017a;Mawhinney et al 2017b), has been suggested to reduce delayed onset muscle soreness (Leeder et al 2012;Roberts et al 2014;Hohenauer et al 2015) and muscle oedema/swelling (Yanagisawa et al 2003;Yanagisawa et al 2004;Vaile et al 2008;Roberts et al 2014), improve recovery of muscle function/performance (Vaile et al 2008;Vaile et al 2011;Versey et al 2013;Roberts et al 2014) and increase gene expression of molecular markers of endurance exercise adaptation (Ihsan et al 2014;Joo et al 2016;Allan et al 2017). CWI, primarily as a result of its ability to decrease tissue temperature and blood flow (Gregson et al 2011;Costello et al 2012;Gregson et al 2013;Mawhinney et al 2013;Mawhinney et al 2017a;Mawhinney et al 2017b), has been suggested to reduce delayed onset muscle soreness (Leeder et al 2012;Roberts et al 2014;Hohenauer et al 2015) and muscle oedema/swelling (Yanagisawa et al 2003;Yanagisawa et al 2004;Vaile et al 2008;Roberts et al 2014), improve recovery of muscle function/performance (Vaile et al 2008;Vaile et al 2011;…”
Section: Introductionmentioning
confidence: 99%